APLIKASI KOMPOS KULIT BUAH KAKAO PADA BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Helviana, Roza '; ', Sampurno '; ', Islan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to determine the effect of cocoa pods compost and the best dosage on the growth of cocoa seedlings. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau, Bina Widya Campus KM 12,5 Simpang Baru, Tampan District, Pekanbaru. The experiment was conducted for 4 month started from Februari until June 2016. The research used Completely Randomized Design (CRD), which consist of 8 treatment that are: K1= 0 g/polybag, K2= 25 g/polybag, K3 = 50 g/polybag, K4= 100 g/polybag, K5= 125 g/polybag, K6= 150 g/polybag, K7= 175 g/polybag, 3 replications for each treatment, so that there are 24 experimental units. Each experimental units consisted of three plants. So the total crop was 72 plants and 2 plants from each experimental unit become sample. Data obtained result were statisticall analyzed by analysis of variance and further test of Honestly Significant Difference at 5%. Parameters observed are seedling height, stem diameter, leaves number, leaf area, the ratio of crown roots, and seedling dry weight. The result of the research show that application of cocoa pods compost gave significant effect to the parameter of seedling height, leaves number and leaf area, and non significant effect to the parameter of stem diameter, the ratio of crown roots and seedling dry weight. The application of cocoa pods compost 50 g/polybag gave good effect to the growth of cocoa seedlings. Keyword :Cocoa, Cocoa pods compost